2019
DOI: 10.3329/bjms.v18i4.42911
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring ‘enzyme only’ Anti-E antibody: A Rare Occurrence

Abstract: Naturally occurring anti-E, present without obvious antigenic stimulation is a rare occurrence of red cell antibody of the Rh blood group system. It is mentioned that such naturally occurring anti-E react only with enzyme modified E-positive red cells. This case report describes a rare case of naturally occurring anti-E in a patient with autoimmune haemolytic anaemia (AIHA). Bangladesh Journal of Medical Science Vol.18(4) 2019 p.818-819

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Naturally, occurring anti-E has been described, but it is a rare entity and there are no reports of it causing hemolytic disease of the newborn or a DHTR. [20][21][22] These naturally occurring anti-E antibodies often only react with papain treated E-positive RBCs, 21,22 and in our case there was clear reactivity without enzyme treatment. Antibody evanescence is common; one study of alloimmunized patients with SCD found that 81% of patients had at least one RBC alloantibody that evanesced during a 2-year time period.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Naturally, occurring anti-E has been described, but it is a rare entity and there are no reports of it causing hemolytic disease of the newborn or a DHTR. [20][21][22] These naturally occurring anti-E antibodies often only react with papain treated E-positive RBCs, 21,22 and in our case there was clear reactivity without enzyme treatment. Antibody evanescence is common; one study of alloimmunized patients with SCD found that 81% of patients had at least one RBC alloantibody that evanesced during a 2-year time period.…”
Section: Discussionmentioning
confidence: 51%
“…Over time his anti‐E likely waned, consistent with his negative pre‐transfusion antibody screen upon presentation to our institution. Naturally, occurring anti‐E has been described, but it is a rare entity and there are no reports of it causing hemolytic disease of the newborn or a DHTR 20–22 . These naturally occurring anti‐E antibodies often only react with papain treated E‐positive RBCs, 21,22 and in our case there was clear reactivity without enzyme treatment.…”
Section: Discussionmentioning
confidence: 53%
“…9,10 ABO antibodies specifically are thought to develop early in life secondary to exposure to microbial glycans that share homology with ABO-antigens. [10][11][12] Rare cases of presumed naturally occurring anti-E and anti-K in the absence of known transfusion-or pregnancy-related exposure have been reported in the literature [12][13][14][15][16][17] and may be secondary to molecular mimicry mechanisms. However, these cases are challenging to confirm definitively due to the fragmentation of the healthcare and medical record system, as well as the potential for exposure to fetal antigens from pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, individual with negative E antigen is common among the Malay population, accounting for about 77% of the population [27]. In addition, anti-E can also be a naturally occurring antibody that may present without a sensitizing event [13,28,29]. However, we could not distinguish between naturally occurring or immune anti-E as all the reactions observed with the cells panel were more intense in the enzymatic medium than in the presence of AHG.…”
Section: Rbc Alloantibody Specificity Among Alloimmunized Patientsmentioning
confidence: 98%